Current trends in the development and teaching of the four language skills - Usó Juan, Esther; Martínez Flor, Alicia (Studies on language acquisition, 2006)
Current Trends in the Development and Teaching of the four Language Skills builds connections from theory in the four language skills to instructional practices and comprises twenty-one chapters that are grouped in five sections. The introductory chapter presents a communicative competence framework in order to highlight the key role the four language skills play in language learning and teaching. The next four sections each represent a language skill. Each section begins with a chapter which briefly illustrates advances in the understanding of how each skill is likely to be learned and taught.